(untitled) (SUNGKAI: Jurnal Aqidah dan Filsafat Islam, 2024)
This study examines the tradition of performing the drama of missing children in wedding rituals in Limbur Merangin Village, West Pamenang District, Merangin Regency. This study is motivated by the low public awareness of the values contained in the tradition. The purpose of the research is to reveal the cultural values, beliefs, and customs contained in this tradition. This study uses a qualitative approach used with data collection methods through observation, interviews, and documentation. The research subjects include traditional leaders, religious leaders, community leaders, and residents of Limbur Merangin Village. Data analysis was carried out descriptively with validity tests through triangulation. The results of the study show that the tradition of lost children’s drama aims to remember and prevent the repetition of past events, and contains important values for cultural preservation. The researcher recommends the public to understand and preserve this tradition as a valuable heritage throughout the ages.